A predictive parameter for the shape memory behavior of thermoplastic polymers. Issue 14 (5th January 2016) - Xiao, Rui; Yakacki, Christopher M.; Guo, Jingkai; Frick, Carl P.; Nguyen, Thao D.
ABSTRACT: We present an experimental and modeling study of the effect of programming conditions on the shape‐memory behaviors of amorphous thermoplastic polymers. Experimentally we measure the influence of deformation temperature, strain rate and relaxation time on the thermomechanical properties and shape‐memory response of poly(para‐phenylene), which is a stiff and strong aromatic thermoplastic. To understand the underlying mechanism, we develop a viscoelastic model, which contains multiple discrete relaxation processes with broad distribution of relaxation time. The model parameters of the relaxation spectrum are obtained from the master curve of small strain–stress relaxation tests using time‐temperature superposition. The model predictions show good agreement with experimental observations, including the stress response and shape‐memory response under various conditions. We applied the model to study the effect of the programming conditions on the shape recovery performance. The results show that the relaxation modulus at the end of the programming process was a predictor of the recovery speed and recoverable strain ratio. This provides a design metric to optimize the shape programming process for shape recovery. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2016, 54, 1405–1414 Abstract : An experimental and modeling study of the effect of programming conditions on the shape memory behaviors of amorphous thermoplastic polymers is presented. The model predictions showed excellent agreement with the experiments regarding the stress response and shape memory response. The results show that the relaxation modulus at the end of the programming process was a predictor of the recovery speed and recoverable strain ratio. This provides a design metric to optimize the shape programming process for shape recovery.